Estimation of the burden of catastrophic costs among the TB affected families of West Bengal, India: a secondary analysis of the sub-national certification survey data - Dey, Abhijit; Ramachandran, Ranjani; Deka, Dhrubajyoti; Biswas, Reetika; Chaklader, Biswajit; Basu, Rajat; Sengupta, Bandita; Roy, Sandip; Basu, Poulami; Keshri, Simran; Pandey, Krishan Kumar (International Journal Of Community Medicine And Public Health, 2025)
Background: Reducing catastrophic costs due to TB is one of the major targets of TB elimination, but there is little data available in India. A sub-national certification (SNC) survey was conducted in 105 clusters of 13 revenue districts of West Bengal. The purpose of this study was to calculate the catastrophic cost and its associations using the SNC data of West Bengal. Methods: A cross-sectional study was conducted using the secondary data collected through SNC survey during December-2022-January-2023. 483 participants having history of TB were included in the study. Results: 26.1% families were found to be affected with catastrophic cost due to TB. The mean annual family income was 691 USD (SD=806). Mean total cost incurred due to TB was 149 USD (SD=1208) including out of pocket of expenditure of 91 USD (SD=1147) and indirect costs of 58 USD (SD=200). No association of catastrophic cost was found with age, gender, religion, socio-clinical vulnerability or cash benefit received status. Those who were labourers, clinically diagnosed, diagnosed at private facilities, treatment duration more than six months and belonging to family below poverty line were found to be independently associated with higher being odds of affected with catastrophic costs. Conclusions: Despite free medicine and free diagnostics many families are still facing catastrophic costs due to TB. Cash benefits should be prioritized towards most impoverished sector of the society. The National TB Elimination Program should also strategize to reduce indirect costs due to wage loss and productivity loss.